Tumor-specific regulatory T cells from the bone marrow orchestrate antitumor immunity in breast cancer - Ge, Yingzi; Böhm, Hans-Henning; Rathinasamy, Anchana; Xydia, Maria; Hu, Xiaoying; Pincha, Mudita; Umansky, Ludmila; Breyer, Christopher; Hillier, Michael; Bonertz, Andreas; Sevko, Alexandra; Domschke, Christoph; et al. (Cancer immunology research, 2019)
Endogenous antitumor effector T-cell responses and immune-suppressive regulatory T cells (Treg) critically influence the prognosis of patients with cancer, yet many of the mechanisms of how this occurs remain unresolved. On the basis of an analysis of the function, antigen specificity, and distribution of tumor antigen-reactive T cells and Tregs in patients with breast cancer and transgenic mouse tumor models, we showed that tumor-specific Tregs were selectively activated in the bone marrow (BM) and egressed into the peripheral blood. The BM was constantly depleted of tumor-specific Tregs and was instead a site of increased induction and activity of tumor-reactive effector/memory T cells. Treg egress from the BM was associated with activation-induced expression of peripheral homing receptors such as CCR2. Because breast cancer tissues express the CCR2 ligand CCL2, the activation and egress of tumor antigen-specific Tregs in the BM resulted in the accumulation of Tregs in breast tumor tissue. Such immune compartmentalization and redistribution of T-cell subpopulations between the BM and peripheral tissues were achieved by vaccination with adenoviral vector-encoded TRP-2 tumor antigen in a RET transgenic mouse model of spontaneous malignant melanoma. Thus, the BM simultaneously represented a source of tumor-infiltrating Tregs and a site for the induction of endogenous tumor-specific effector T-cell responses, suggesting that both antitumor immunity and local immune suppression are orchestrated in the BM.